PEMETAAN PELATIHAN PENULISAN ARTIKEL ILMIAH UNTUK MENDUKUNG PROFESIONALISME GURU - Emaliana, Ive (Faculty of Cultural Studies, Universitas Brawijaya, 2021)
In addition to teaching, teachers are expected to have the ability to write scientific papers as part of their professional development. The challenges teachers face in writing scientific papers are largely due to limited time for research and a lack of understanding of the rules for writing scientific papers. The aim of this community service program is to map the needs of English teachers in improving their professionalism through scientific writing. The method used to achieve this objective is to conduct research and article writing mentoring for journals, totaling at least 30 hours of face-to-face or online sessions. This community service is a replication of last year's initiative, which was implemented in collaboration with the English Language Teachers' Association (MGMP) of Senior High Schools and Vocational Schools across Malang City. This previous initiative proved effective and successfully assisted six teachers in publishing journal articles. This community service initiative is being implemented for English teachers in the districts of Malang and Batu City. Through this activity, it is hoped that the challenges and obstacles faced by English teachers in writing scientific papers to enhance professionalism will be identified.